marcadores de realidad en las telenovelas mexicanas y su uso en el aula de ELE - Grimm, Anja (Huarte de San Juan. Filología y Didáctica de la Lengua, 2021)
The use of audiovisuals in the SFL classroom has increased significantly during the lst years and cinema and tv have become a highy exploited resource for didactica materials. Nevertheless, hispanic soap operas have received very little attention until today. As for all the authentic resources, in case of considering Mexican soap operas as real input to teach sociocultural and linguistic contents in Spanish foreign language teaching, it is of utmost importance to determine the degree of realism reflected in them. This article covers a brief analysis of the reality markers which are present in Mexican soap operas and which justify the suitability of using the tv genre as a teaching resource. Those markers are geographic, linguistic and sociocultural. The investigation has been conducted from the perspective of critical discourse analysis which allows a consistent approach to the treatment of the contents. In summary, it can be pointed out that Mexican soap operas offer a satisfactory degree of reality markers which make them a worthwhile input in SFL teaching. For the sake of iving the students a critical approach to Mexico, its culture and linguistic varieties and in order to maximise the didactic potential of Mexican soap operas, teachers should follow some guidelines which will be outlined in this article.